2008
DOI: 10.1007/s11156-008-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity commonality and spillover in the US and Japanese markets: an intraday analysis using exchange-traded funds

Abstract: Exchange traded funds, Commonality, Intraday liquidity,  G14, G15,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Since there are different decision-making time scales among traders, the true structure of such spillovers will vary over different time scales associated with those different horizons. In rare collaboration to this subject, [23] examine intraday returns and liquidity patterns of Japanese exchange-traded funds. Their findings suggest that some commonality exists in the returns and liquidity of these apparently different assets.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are different decision-making time scales among traders, the true structure of such spillovers will vary over different time scales associated with those different horizons. In rare collaboration to this subject, [23] examine intraday returns and liquidity patterns of Japanese exchange-traded funds. Their findings suggest that some commonality exists in the returns and liquidity of these apparently different assets.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the case of the 'open-to-close' period, we dropped the dummy variables in the variance equation so as to account for the opening and closing sessions. 14 An interesting comparison may be made to the study by Datar et al (2008), which observed intraday spillovers between two international ETFs while the spillover effects no longer exist across trading days. …”
Section: Real Time Progress Of Spillover Effectsmentioning
confidence: 99%
“…It has specifically been found that: (1) intraday mean returns and volatility are U-shaped (Wood et al 1985;Harris 1986;Lockwood and Linn 1990;McInish and Wood 1990); (2) intraday trading volume is U-shaped (Harris 1986;Jain and Joh 1988;Viswanathan 1990, 1993;Gerety and Mulherin 1992); and (3) opento-open returns are more volatile than close-to-close returns (Amihud and Mendelson 1987;Stoll and Whaley 1990;McInish and Wood 1991;Chan et al 1996;and Datar et al 2008). These discernible patterns have generated significant interest in the development of theoretical models aimed at explaining such regularities, with several hypotheses having been suggested.…”
Section: Intraday Variations In Spillover Effectsmentioning
confidence: 99%
“…In addition to Asness et al (2013), our empirical analysis is motivated by the prior studies on volatility spillover effects between different international stock markets and across different industries and size groups within markets (see e.g., Hamao et al 1990;Chiang and Chiang 1996;Campbell et al 2001;Ewing 2002;Harris and Pisedtasalasai 2006;Datar et al 2008;Diebold and Yilmaz 2009;Gannon 2010;Wang 2010;Ben Sita 2013;Clements et al 2015;Barunik et al 2016). As noted in the literature, knowledge of potential volatility spillovers has important practical implications for the formulation and implementation of investment, diversification, and risk management strategies.…”
Section: Introductionmentioning
confidence: 99%